KESARJANAAN TRADISIONALIS AL-QUR’AN DI ERA KONTEMPORER: Telaah terhadap The Study Quran a New Translation and Commentary karya Seyyed Hossein Nasr dan Tim - Annas Rolli Muchlisin (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2017)
Two years ago, a Qur’anic translation and interpretation work was published in English which was initiated by Seyyed Hossein Nasr and his team: CanerK. Dagli, Maria Massi Dakake, Joseph E. B. Lumbard, and Mohammed Rustom. The work that they named as the Study Quran A New Translation and Commentary covers both translation and interpretation of the Qur’an in fully 30 chapters, and was added by some essays written by scholars from various academic and country backgrounds. In other side, this work represents Nasr and his team’s thought on “tradition”. For them, tradition is not like was understood by several people who consider it as something old-fashioned, but rather as a set of principles that revealed from God. In some places, this traditionalist insight emerges in their interpretation. This paper attempts to study on the methodology used in the work and to see its position in hermeneutics typology. From that study, it could be seen some interpretation principles held by its authors, such as emphasizing the sacred nature of the Qur’an, explaining that the Qur’an contains all doctrines about reality natures in all of its levels, using universalist perspective in comprehending Qur’anic verses that related to religious traditions, and presenting traditional Qur’anic interpretation.From hermeneutics typology, this work could be categorized in obyektivis-cum-subjektivis interpretation.